Fig abscission as a defense mechanism of Ficus trees against parasitism by non-pollinating fig wasps - Shang-Yang Lin; Bruno Di Giusto; Anthony Bain (Scientific Reports)
Abstract How does the fig tree Ficus benguetensis protect its investment in the production of figs and pollinating fig wasps against parasitism from non-pollinating fig wasps? This study documents a previously overlooked defense mechanism: fig abscission—the natural shedding of the fig fruit as a defense mechanism. Our bagging experiments showed that both the absence of pollination and high parasitism levels lead to the abortion of F. benguetensis figs, with positive correlations between parasitism levels, increased abscission rates, and decreased pollinator production. Moreover, we found that high parasitism corresponds to shortened fig development periods until abscission, while medium parasitism levels result in fewer pollinators. Our findings suggest that abscission may function as a resource conservation strategy, as most of the tree’s investment in the figs occurs post-pollination. This study uncovers for the first time the use of fig abscission as a unique defense against non-pollinating fig wasp parasites, broadening our understanding of plant defense mechanisms within mutualistic interactions.